Guía para el Reconocimiento de Zonas de Agrobiodiversidad en el Perú, Segunda Edición, Bilingüe Español – Quechua - Sotomayor Melo, Diego Alejandro; Carrillo Castillo, Fredesvinda; Berrera Gallardo, Roger; Roldán Chávez, Agripina; Amasifuen Guerra, Carlos Alberto; Guerrero Abad, Juan Carlos (Instituto Nacional de Innovación Agraria, 2020)
79 Páginas